Correction: Shobha et al. Trichoderma-Mediated ZnO Nanoparticles and Their Antibiofilm and Antibacterial Activities. J. Fungi 2023, 9, 133 - Balagangadharaswamy Shobha; Bagepalli Shivaram Ashwini; Mohammed Ghazwani; Umme Hani; Banan Atwah; Maryam S. Alhumaidi; Sumanth Basavaraju; Srinivas Chowdappa; Tekupalli Ravikiran; Shadma Wahab; Wasim Ahmad; Thimappa Ramachandrappa Lakshmeesha; et al. (Journal of Fungi)
In the original article [...]